MEMBANGUN AUDIT YANG BERKELANJUTAN : MENGATASI DISFUNGSI MELALUI PENGUATAN KOMITMEN DAN TEKANAN WAKTU - Putri, Zalfa Azela; Litdia, Litdia (Taksasila Edukasi Insani, 2024)
This study aims to examine the effect of profetional commitment, performance auditor and time pressure on dysfunctional audit behavior. This researxh belongs to the type of quantittive research. The data collection method used is primary data with a field survey method. The technique used is by distributing questionnaires to 85 respondents of external auditors who work in Public Accounting Firms in the South Jakarta area. The sampling techinque used is non probability sampling. Testing the research data is processed using smartPLS version 4.0. The result of this study partially show that profetional commitment doesn’t significant on dysfunctional audit behavior, performance auditor has a prositive and significant effect on dysfucntional audit behavior, and time pressure has a positive and significant effect on dysfunctional audit behavior.Keywords : Profetional Commitment, Performance Auditor, Time Pressure, and Audit Dysfunctional Behavior)